Simulation of the Lightweight Ceramic/Aluminum Alloy Composite Armor for Optimizing Component Thickness Ratios - Chang, Z.-L.; Zhao, W.-L.; Zou, G.-P.; Sun, H.-Q. (Проблемы прочности, 2019)
The lightweight ceramic/aluminum alloy composite armor design is examined and optimized to get better protective performance. The armor penetrability is simulated via the smooth particle hydromechanics approach using the ANSYS/AUTODYN software. The accuracy of the program was verified by comparing with known data. Three composite armor types with the total thickness of 30, 40, and 50 mm, and five different ceramic/metal thickness ratios were analyzed in simulation of the residual bullet speed and the final distance. Simulation results are compared with the theoretical model. The best bullet protective performance of the three armor types was obtained with the ceramic/aluminum alloy thickness ratio of 4:1. Конструкция легковесной брони из композита керамика/алюминиевый сплав рассматривается и оптимизируется для улучшения защитных характеристик. Процесс проникновения в броню моделируется с использованием программы SPH программного обеспечения ANSYS/AUTODYN. Точность метода сглаженных частиц (метод SPH) была подтверждена путем сравнения полученных данных с известными. Рассматривались три типа композитной брони общей толщины 30, 40, 50 мм и с пятью различными отношениями толщина керамики/толщина металла при моделировании остаточной скорости пули и конечной длины. Результаты моделирования сравниваются с теоретической моделью. Лучшие пулезащитные характеристики трех типов брони из керамического композита были получены при отношении толщина керамики/толщина алюминия в композитной броне 4:1. Конструкція легковагій броні з композиту кераміка / алюмінієвий сплав розглядається і оптимізується для поліпшення захисних характеристик. Процес проникнення в броню моделюється з використанням програми SPH програмного забезпечення ANSYS / AUTODYN. Точність методу згладжених частинок (метод SPH) була підтверджена шляхом порівняння полу¬ченних даних з відомими. Розглядалися три типи композитної броні загальної товщини 30, 40, 50 мм і з п'ятьма різними відносинами товщина кераміки / товщина металу при моделюванні залишкової швидкості кулі і кінцевої довжини. Результати моделювання порівнюються з теоретичною моделлю. Кращі кулезахисні характеристики трьох типів броні з керамічного композиту були отримані при співвідношенні товщина кераміки / товщина алюмінію в композитної броні 4: 1. This work was supported by the National Natural Science Foundation of China (Nos. 11602068 and 11602066) and Fundamental Research Funds for the Central Universities (Nos. HEUCFM170203, HEUCFP201744, and HEUCFP201762).